Toward a Run-Time Verification Framework for Real-Time Safety-Critical Systems - Nelissen, Geoffrey (2015)
Presented at SEMINAR "ACTION TEMPS RÉEL:INFRASTRUCTURES ET SERVICES SYSTÉMES". 10, Apr, 2015. Brussels, Belgium.